Surgical reconstruction of ectrodactyly deformity in four dogs - Innes, J. F.; McKee, W. M.; Mitchell, R. A. S.; Lascelles, B. D. X.; Johnson, K. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
Four immature dogs were presented with ectrodactyly. Two dogs were initially treated with distraction osteogenesis of a hypoplastic ulna and all had surgical correction of the cleft deformity. In each case proximal metacarpal apposition with or without carpal arthrodesis formed the basis of surgical treatment. Follow-up information was available for three cases and all showed improved limb function. Corrective surgery appears to be a viable alternative to amputation for treatment of ectrodacty1y.
Keywords: Ectrodactyly; distraction osteogenesis; carpal arthrod esis; dog